Analysis of Risk Factors for the Incidence of Stunting in Toddlers - Andi Sastria Ahmad; Abdul Azis; Fadli (Journal of Health Science and Prevention, 2021)
Stunting may have occurred since prenatal phases until the baby was 2 years old because of malnutrition. Children having stunting have a problem in growth and cognitive impairments. This study aims to analyze the risk factors of stunting among children under five in Empagae, Sidrap Regency. This correlational research study the correlation between posyandu visits, health workers' roles, and parenting on stunting. Technique sampling used was consecutive sampling with 52 respondents. The results showed that there was a moderate correlation between the health workers roles and stunting (p-value = 0.018; r = 0.33), strong correlation between parenting styles and stunting (p. -value = 0.000; r = 0.82), and moderate correlation between posyandu visits stunting (p-value = 0.002; r = 0.43). This research implies that mothers must fulfill nutrition to prevent stunting and be more active in posyandu activities to have nutrition monitoring. It is hoped that health workers have to control and monitor the nutritional status of toddlers, pregnant women, and mothers who have babies to prevent stunting.